Scale effects in GFRP‐bar reinforced concrete beams. (28th February 2023) - Accornero, Federico; Cafarelli, Renato; Carpinteri, Alberto; Nanni, Antonio
Abstract: Glass fiber‐reinforced polymer (GFRP)‐reinforced concrete (RC) can be defined as a cementitious material in which the reinforcing secondary phase consists in corrosion‐resistant GFRP rebars. For this next‐generation structural material, experimental flexural tests highlight how the postcracking response is strongly affected by the amount of GFRP area together with the structural size‐scale. In this work, the cohesive/overlapping crack model (COCM) is adopted to describe the transition between cracking and crushing failures occurring in GFRP‐RC beams by increasing the beam depth, the reinforcement percentage, and/or the concrete compression strength. Within this nonlinear fracture mechanics model, the tensile and compression ultimate behaviors of the concrete matrix are modeled through two different process zones that advance independently one of another. Moreover, this model is able to investigate local mechanical instabilities occurring in the structural behavior of GFRP‐RC beams: tensile snap back and snap‐through, which are due to concrete cracking and reinforcement bridging action, and the compression snap‐back generated by the unstable growth of the crushing zone. In this context, the application of the COCM highlights that the ductility, which is represented by the plastic rotation capacity of the GFRP‐RC beam only when the reinforcement can slip, decreases as reinforcement percentage and/or beam depth increase. In this way, rational and quantitative definitions of hyperstrength and brittle compression crushing behaviors can be provided as a GFRP percentage depending on the beam depth.